Evaluación de la actividad depresora de etomidato en dos concentraciones en trucha arcoíris (Onchorhyncus mykiss) - Messina, Maria Jimena (2025)
The aim of this study was to evaluate the depressing activity of etomidate at concentrations of 1 and 2 ppm/L in rainbow trout from an intensive breeding system in Córdoba, Argentina. The use of the anaesthetic, regardless of the dose, produced a reduction in respiratory frequency between 61 and 66% in anaesthesia compared to the basal respiratory frequency (p<0.05). The times of partial and total loss of equilibrium and in anaesthesia were statistically lower (p<0.05) at the dose of 2 ppm/L, while the recovery time did not present significant differences (p>0.05) between groups. The concentrations used induced a dose-dependent state of anaesthesia that allows the manipulation of the fish without adverse effects that compromise the life of the fish.